2012
DOI: 10.1155/2012/268781
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Counter DoS Attacks in Mobile IP Communication

Abstract: Similar to wired communication, Mobile IP communication is susceptible to various kinds of attacks. Of these attacks, Denial of Service (DoS) attack is considered as a great threat to mobile IP communication. The number of approaches hitherto proposed to prevent DoS attack in the area of mobile IP communication is much less compared to those for the wired domain and mobile ad hoc networks. In this work, the effects of Denial of Service attack on mobile IP communication are analyzed in detail. We propose to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Kandah et al [6] have tried to introduce the behavior of adversary that initiate a Colluding attacks on nodes which aims to disturb the packet transmission process with hiding their identity and existence and in the same way Moudni et al [7] have studied and investigated the performance of AODV routing protocol under various attacks and it is found that of impact of attacks decreases the performance of MANET. Pravin et al [8] have examined the impact of DoS attacks and gave a novel method of packet filtering that works to detect compromised nodes and to enhance the performance of operational functionalities of networks. Qin and Huang [9] have designed a new strategy based on position based routing approach that compromise the transmission anonymity of MANET and identifies end-to-end flow between source and destination with maximum accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Kandah et al [6] have tried to introduce the behavior of adversary that initiate a Colluding attacks on nodes which aims to disturb the packet transmission process with hiding their identity and existence and in the same way Moudni et al [7] have studied and investigated the performance of AODV routing protocol under various attacks and it is found that of impact of attacks decreases the performance of MANET. Pravin et al [8] have examined the impact of DoS attacks and gave a novel method of packet filtering that works to detect compromised nodes and to enhance the performance of operational functionalities of networks. Qin and Huang [9] have designed a new strategy based on position based routing approach that compromise the transmission anonymity of MANET and identifies end-to-end flow between source and destination with maximum accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…For this reason we will compare our protocol with those striving to counteract DoS attacks in MANETs. Denial of Service (DoS) attacks for ad hoc networks have been studied in [1,32,48], but in these works advertisement flooding is not addressed.…”
Section: Comparison With Related Workmentioning
confidence: 99%
“…With the local area wireless communication having become increasingly popular, Wi-Fi, ZigBee, Bluetooth, RFID and relevant wireless networks technologies [1] have become more common in our daily lives. Security issues [2] sometimes viewed as a standalone component, however, must be emphasized, since systems designed without security can become weakness. Security is one of the most important issues in wireless communication given that data are transmitted through the air.…”
Section: The Concept Of Random Interval Fingerprint In Pervasive Commmentioning
confidence: 99%